Zhe cai shi fu wu she ji yi bu you quan qiu fu wu she ji shi gong tong da zao de ju zuo = This is service design doing / = This is service design doing - Stickdorn, Marc; Hormess, Markus; Lawrence, Adam; Schneider, Jakob (Ren min you dian chu ban she = Posts & Telecom Press, 2022)
Detailed summary in vernacular field.
880-05;O'Reilly Media, Inc. shou quan chu ban
Keywords: Service industries -- Management; Customer services; Services (Industrie); Gestion; Service à la clientèle